Compound Words in Balinese - Ni Putu Parmini; I Wayan Mawa; I Made Suparta; I Gede Bagus Wisnu Bayu Temaja (Westscience Press, 2024)
This study aimed to identify the forms and meanings of compound words in Balinese. The data were collected from Balinese speakers, literature, and the researcher’s intuition as a Balinese speaker. In data analysis, it implemented distributional and referential (identity) methods. The research results were presented in formal and informal manners. The results found that Balinese compounds have noun, verb, and adjective classes. Noun compound words have these construction patterns: noun + noun, noun + verb, and noun + adjective. Verb compound words only have verb + noun patterns. Adjective compound nouns have adjective + adjective and adjective + pre-categorical patterns. Furthermore, there are eleven meanings found in compound words, such as utility, place, time, jurisdiction, similarity in forms, to be like habitat, opposite mixed nature, like its origin, resemblance, and intensity.